The Relationship of Music Therapy In Reducing Stress Levels In Pregnant Women at the Army Hospital of Padang Sidimpuan City - Panggabean, Harisa; Lubis, Doli (Jurnal Psikologi, 2025)
Background Maternal stress during pregnancy can harm both the mother and fetus, increasing the risk of complications such as preterm birth and low birth weight. Music therapy serves as a non-pharmacological method to reduce anxiety and improve emotional well-being by influencing the autonomic nervous system and lowering cortisol levels. Objective This study examined the relationship between music therapy and stress levels among pregnant women at Padangsidimpuan Military Hospital, Indonesia. The Methods is A quantitative correlational design was used with 35 pregnant women selected through purposive sampling. Stress was measured using the Perceived Stress Scale (PSS), and data were analyzed using Pearson’s Product-Moment Correlation (p < 0.05). Results: A significant negative correlation was found between music therapy and stress levels (r = –0.45, p < 0.01). Regular listening to instrumental or relaxation music was associated with lower stress scores. Conclusion Music therapy is an effective and practical non-pharmacological intervention for reducing prenatal stress and should be considered as part of antenatal care.